Geochemical assessment of potential sources for nitrate in the wasia aquifer, Al Kharj Area, central Saudi Arabia - Khogali, Abid; Birkle, Peter; Al-Shaibani, Abdulaziz; Keller, Martin; Tawabini, Bassam; Makkawi, Mohammad (Water, 2020)
Nitrate (NO3-) represents one of the major groundwater constituents with increasing distribution and concentration in the Kingdom of Saudi Arabia. This study aimed to determine potential sources of nitrate in the Early to Late Cretaceous Wasia aquifer system at the Al Kharj area (Central Saudi Arabia) by an integrative approach using groundwater geochemistry, nitrate isotopes (15N-NO3 and 18O-NO3), and tritium (3H) measurements. The lowest saline groundwater samples (TDS = 1400-2000 mg/L) from the peripheral zone were representative for pristine groundwater from theWasia aquifer with nitrate concentrations below 20 mg/L and low 18O-NO3 ratios (8.7-20.6%) but enriched 15N-NO3 values (up to 10.8‰). In contrast, 11 out of 34 analyzed water samples from irrigation wells and cattle watering wells exceeded the World Health Organization (WHO) drinking water guideline value for nitrate of 50 mg/L with maximum concentrations of up to 395 mg/L. Nitrate fertilizers and atmospheric deposition are the main sources of nitrate in groundwater in the eastern and northern sections of the study area. The combination of elevated salinities (4940-7330 mg/L), NO3 (111-395 mg/L), boron (516-1430 μg/L), and enriched 18O-NO3 (21.7-25.8‰) ratios with depleted 15N-NO3 (5.7-7.6‰) confirm the local influx of evaporated irrigation water with remnants of dissolved fertilizer into the Wasia groundwater system. There was no evidence for the influx of animal or human wastes from adjacent dairy, poultry, and housing infrastructures. Tritium concentrations below the detection limit of 0.8 TU for most borehole samples implied the absence of recent natural recharge. The estimated annual average N influx of 3.34 to 6.67 kg/ha to theWasia aquifer requires a combination of atmospheric deposition and anthropogenic sources (mainly nitrate fertilizers) to increase the nitrogen content of the Wasia aquifer.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Geochemistry; Nitrate sources; Stable isotopes; Wasia aquifer